Multi-Stage Fast Charging Technique for Lithium Battery in Photovoltaic systems - Yong, Syakirin O.; Rahim, Nasrudin A.; Eid, Bilal M.; Tankut, Buray (Institute of Electrical and Electronics Engineers Inc., 2022)
In renewable energy resources such as photovoltaic (PV) systems, fast charging is an emerging case for the battery charger. In this paper, constant-current (CC) and constant-voltage (CV) charging scheme has been studied since it has the highest possible reliability for lithium based batteries. In this work a new charging technique to expedite charging time is proposed. This is a multi-stage technique which improves the threshold voltage detection during CC-stage. Thus the transition to CV-stage occurs accurately at the knee voltage. The novelty of the proposed technique is in the charging algorithm. An experiment was setup based on PIC18f4520 microcontroller. The performance of the proposed technique and the conventional CC-CV Li-ion battery charger has been compared. The result of the proposed technique shows that there is 20% improvement in charging time compared to the conventional CC-CV Li-ion battery charger. © 2022 IEEE.
Keywords: charger; constant current; constant voltage; lithium-ion; PV system; renewable Energy